2010
DOI: 10.1161/circresaha.109.213900
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of SM22 Promotes Inflammation After Artery Injury via Nuclear Factor κB Activation

Abstract: Rationale: SM22 (or transgelin), an actin-binding protein abundant in vascular smooth muscle cells (VSMCs), is downregulated in atherosclerosis, aneurysm and various cancers. Abolishing SM22 in apolipoprotein E knockout mice accelerates atherogenesis. However, it is unclear whether SM22 disruption independently promotes arterial inflammation. Objective: To investigate whether SM22 disruption directly promotes inflammation on arterial injury and to characterize the underlying mechanisms. Methods and Results: Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 36 publications
(48 reference statements)
8
82
1
Order By: Relevance
“…Reduced expression of transgelin-1 (sm22a) is related to VSMC proliferation and atherosclerotic plaque formation (Feil et al 2004;Shen et al 2010). Transgelin expression was strongly downregulated in the aorta of mice fed a highfat and combined B vitamin-depleted diet.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of transgelin-1 (sm22a) is related to VSMC proliferation and atherosclerotic plaque formation (Feil et al 2004;Shen et al 2010). Transgelin expression was strongly downregulated in the aorta of mice fed a highfat and combined B vitamin-depleted diet.…”
Section: Discussionmentioning
confidence: 99%
“…VSMC in SM22 KO mice had increased NF-B activation upon carotid arterial injury with greater adhesion molecule expression possibly related to greater ROS production associated with cytoskeletal disruption (1614).…”
Section: Continuedmentioning
confidence: 96%
“…These data suggest that disruption of SM22␣ may be responsible for activation of p47 phox and ROS production in VSMCs, as previously shown. 15 Phosphorylation of SM22␣ at Ser181 Mediates P47 phox Activation and ROS Production Via Promoting Interaction of PKC␦ With P47 phox It has been known that Ang II-induced ROS production occurs in early and later 2 phases. 25,26 To confirm the possible roles of SM22␣ in early oxidative stress, based on 3 potential phosphorylation sites in SM22␣, 16 an immunoprecipitation assay was performed to examine the phosphorylation of SM22␣.…”
Section: Disruption Of Sm22␣ Is Required For the Phosphorylation Of Pmentioning
confidence: 99%
“…The latest study has revealed that the disruption of smooth muscle (SM) 22␣, an actin-associated protein, induces vascular inflammation through activation of ROS-mediated NF-B pathways. 15 SM22␣ is a member of the calponin family, containing a calponin homology domain conserved from yeast to human. 16,17 The known function of SM22␣ is to bundle and stabilize actin filaments, which is involved in actin filament assembly and cytoskeletal rearrangements.…”
mentioning
confidence: 99%
See 1 more Smart Citation